Utilization Of Technology In Academic Supervision - Carona Elianur (Justek : Jurnal Sains dan Teknologi, 2022)
Abstract:  The use of technology has now penetrated all aspects, including the education aspect. Education Supervision as education quality assurance has also used technology in the process. This article aims to find out the technology used in academic supervision, as well as to explore the advantages of that technology. The research method used is a literature review; the data source is scientific articles from the Google Scholar database. Data retrieval using the help of the Publish or Perish (harzing) application. The research results found that the technologies used in the supervision of education were: Google Form Applications, Zoom Meeting Applications, Google Spreadsheet Applications, Web-Based Technology, E-Quality Supervision Applications, and Online Internet-Based Technologies. Many advantages are found in the use of this technology, namely: effective and efficient supervision process, supervision can be done online, the collected data can be accessed online, and the data is appropriately archived. The results of this study recommend the use of technology in academic supervision in order to achieve effective and efficient academic supervision.Abstrak: Pemanfaatan teknologi saat ini sudah merambah seluruh aspek, tak terkecuali aspek Pendidikan. Supervisi Pendidikan sebagai penjaminan mutu Pendidikan juga sudah menggunakan teknologi dalam prosesnya. Artikel ini bertujuan untuk mengetahui teknologi yang digunakan dalam supervisi akademik, serta mengekplorasi keunggulan dari teknologi tersebut. Metode penelitian yang digunakan berupa literature review, sumber data berupa artikel ilmiah yang diambil dari data base google scholar. Pengambilan data menggunakan bantuan aplikasi Publish or Perish (harzing). Hasil penelitian ditemukan teknologi yang dimanfaatkan dalam supervisi Pendidikan berupa: Aplikasi Google Form, Aplikasi Zoom Meeting, Aplikasi Google Spreadsheet, teknologi Berbasis Web, Aplikasi E-Supervisi Mutu, dan Teknologi Berbasis Internet Online. Banyak keuntungan yang ditemukan dalam pemanfaatan teknologi ini, yaitu: efektif dan efisiennya proses supervisi, supervisi dapat dilakukan secara daring, data yang terkumpul dapat diakses secara online, serta data-data terarsip dengan baik. Hasil penelitian ini merekomendasikan untuk penggunaan teknologi dalam supervisi akademik, demi tercapainya supervisi akademik yang efektif dan efisien.